2022
DOI: 10.1016/j.bja.2021.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Review of the requirements for effective mass casualty preparedness for trauma systems. A disaster waiting to happen?

Abstract: Mass casualty incidents (MCIs) are diverse, unpredictable, and increasing in frequency, but preparation is possible and necessary. The nature of MCIs requires a trauma response but also requires effective and tested disaster preparedness planning. From an international perspective, the aims of this narrative review are to describe the key components necessary for optimisation of trauma system preparedness for MCIs, whether trauma systems and centres meet these components and areas for improvement of trauma sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 88 publications
2
11
0
Order By: Relevance
“…Law force, fire departments, Red Crescent, specialized organizations of hazardous materials, and so forth are among the partners of the EMS in the management of MCIs. Coordination and collaboration of intra‐ and interorganizations were one of the key components that were extracted from this study 1,10,19 . This important issue in the study conducted by Sadat in Iran in the field of EMS preparedness in mass casualty traffic accidents was one of the important findings of this qualitative study which was consistent with the findings of the present study 20 .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Law force, fire departments, Red Crescent, specialized organizations of hazardous materials, and so forth are among the partners of the EMS in the management of MCIs. Coordination and collaboration of intra‐ and interorganizations were one of the key components that were extracted from this study 1,10,19 . This important issue in the study conducted by Sadat in Iran in the field of EMS preparedness in mass casualty traffic accidents was one of the important findings of this qualitative study which was consistent with the findings of the present study 20 .…”
Section: Discussionsupporting
confidence: 83%
“…Coordination and collaboration of intra-and interorganizations were one of the key components that were extracted from this study. 1,10,19 This important issue in the study conducted by Sadat in Iran in the field of EMS preparedness in mass casualty traffic accidents was one of the important findings of this qualitative study which was consistent with the findings of the present study. 20 The findings of the study conducted by Kondo in Japan showed that to provide constant medical assistance at the disaster area, logistic teams, and other disaster medical relief teams must have constant coordination at the medical headquarter command.…”
Section: F I G U R Esupporting
confidence: 90%
See 3 more Smart Citations